On ss-quasinormal and weakly s-supplemented subgroups of finite groups - Li, C.; Li, Yangming (Ukrains’kyi Matematychnyi Zhurnal, 2011)
Suppose that G is a finite group and H is a subgroup of G. H is called ss-quasinormal in G if there is a subgroup B of G such that G = HB and H permutes with every Sylow subgroup of B; H is called weakly s-supplemented in G if there is a subgroup T of G such that G = HT and H T ≤ H_sG, where H_sG is the subgroup of H generated by all those subgroups of H which are s-quasinormal in G. In this paper we investigate the influence of ss-quasinormal and weakly s-supplemented subgroups on the structure of finite groups. Some recent results are generalized and unified.